Tipe Kepribadian pada Mahasiswa Kelas Manajemen Universitas Bina Nusantara dengan Menggunakan Myers-Briggs Type Indicator (MBTI) - Son Wandrial (Bina Nusantara University, 2014)
This article was made to identify the personality type of students I teach using the MBTI models. There are 32 standard questions in the questionnaire, and students are asked to choose one of two available answers for each question. Furthermore, students return all questionnaires had been answered, and the researcher calculates and gives the scores to the answers given referring to the four types of the MBTI whether the student is in the category: Extrovert-Introvert, Sensing-Intutive, Thinking-Feeling, and Judging-Perceiving. There are 16 personality types in the MBTI. The question took from the book Richard L Daft. The results show the majority of students is extroversion type in approximately 60.31%, and the rest is introversion type and about 58.78% of students are sensing type.